Integrating drone-borne thermal imaging with artificial intelligence to locate bird nests on agricultural land - Santangeli, Andrea; Chen, Yuxuan; Kluen, Edward; Chirumamilla, Raviteja; Tiainen, Juha; Loehr, John (Nature Publishing Group, 2020)
In conservation, the use of unmanned aerial vehicles (drones) carrying various sensors and the use of deep learning are increasing, but they are typically used independently of each other. Untapping their large potential requires integrating these tools. We combine drone-borne thermal imaging with artificial intelligence to locate ground-nests of birds on agricultural land. We show, for the first time, that this semi-automated system can identify nests with a high performance. However, local weather, type of arable field and height of the drone can affect performance. The results’ implications are particularly relevant to conservation practitioners working across sectors, such as biodiversity conservation and food production in farmland. Under a rapidly changing world, studies like this can help uncover the potential of technology for conservation and embrace cross-sectoral transformations from the onset; for example, by integrating nest detection within the precision agriculture system that heavily relies on drone-borne sensors.
Keywords: aerial vehicles; bird nests; artificial intelligence